UPAYA MENINGKATKAN HASIL BELAJAR KETERAMPILAN GERAK DASAR ANAK MELALUI PENDEKATAN BERMAIN - Andy Widhiya Bayu Utomo (Universitas Pendidikan Mandalika, 2019)
the aims of this study is to improve the basic motion skills of children through the approach to play on the seventh grade students of SMP Kedunggalar Lesson Year 2015/2016. This research uses Class Action Research method (PTK). The data source of this research is the students of class VII SMP KEDUNGGALAR Ngawi academic year 2015/2016 amounted to 76 people consisting of 37 students VIIA and 39 students class VIIB. Technique of collecting data with observation and assessment of learning result of basic movement skill. Data analysis technique used in this research is descriptive based on quantitative analysis with percentage. Based on the result of the research, it can be concluded that the use of play approach method can improve the learning outcomes of the students' movement of the class VII SMP KEDUNGGALAR Ngawi in academic year 2015/2016. From the analysis result obtained significant improvement from pre cycle, cycle I and cycle II. The basic motion of children in the pre cycle in the complete category is 51 students. In cycle I in the category of complete is 55 students. While in cycle II there is an increasing number of mastery of student learning outcomes to 64 students in the complete category. The conclusion of this research is the use of play approach can improve the learning result of Basic Motion Skill of VII Junior High School students of SMP Kedunggalar Academic Year 2015/2016.